2021
DOI: 10.3390/jcm10153434
|View full text |Cite
|
Sign up to set email alerts
|

Role of Annual Influenza Vaccination against Lung Cancer in Type 2 Diabetic Patients from a Population-Based Cohort Study

Abstract: Type 2 diabetes mellitus (DM) patients are at a higher risk for developing lung cancer due to immune dysfunction and chronic inflammation. They also have increased morbidity and mortality related to influenza, and it is recommended that they receive an annual influenza vaccination. In this study, we evaluate whether influenza vaccination could reduce the incidence of lung cancer in DM patients. This cohort study included DM patients (≥55 years old) between 1 January 2002 and 31 December 2012 by using the Taiwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…The dose-dependent protective effect of the influenza vaccination for all ages and both sexes (significantly for individuals aged >75 years) was also identified in our other studies [ 24 , 25 ]. Influenza vaccination-related immunomodulation might explain this phenomenon.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The dose-dependent protective effect of the influenza vaccination for all ages and both sexes (significantly for individuals aged >75 years) was also identified in our other studies [ 24 , 25 ]. Influenza vaccination-related immunomodulation might explain this phenomenon.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, the Taiwanese government has recommended an annual government-funded influenza vaccination for high-risk individuals since 1998 [ 23 ]. In our previous studies, we observed that influenza vaccination could protect patients with chronic lung disease [ 24 ] and diabetes mellitus [ 25 ] from the risk of lung cancer. Whether influenza vaccination reduces the risk of lung cancer among patients with hypertension has yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, influenza vaccination has been shown to reduce the risk for pneumonia-/influenza-related hospitalizations and mortality [ 61–63 ]. Our previous study also revealed a reduction in the risk of lung cancer with influenza vaccination among diabetic patients [ 64 ]. Another study indicated that the frequency and severity of influenza infections were positively related to the risk of lung cancer events [ 65 ], however, the relation between many other solid cancers and influenza events is still unclear.…”
Section: Discussionmentioning
confidence: 87%
“…In 1995, Taiwan’s National Health Insurance (NHI) program was established to provide the residents of Taiwan with comprehensive health insurance. This program currently covers more than 98% of the population in Taiwan ( Luo et al, 2020 ; Chen et al, 2021 ; Zheng et al, 2021 ). In this study, the statistical characteristics of the sample group were similar to those of the general population.…”
Section: Methodsmentioning
confidence: 99%